EVALUASI SETTING DISTANCE RELAY PADA SUTT 150 KV ANTARA GI PAMONA – GI SIDERA - Adrianto, J; Sarjan, Muhammad; Rahman, Yuli Asmi (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2016)
A short circuit is a common fault of overhead lines. In 2015, short circuit caused by surge lighting and fallen trees, occurred four times in transmission line connected PamonaSiderasubstation. In securing transmission line, distance relay should be applied as the primery protection. However, incorrect setting of relay may readily lead to relay failure to protect the line. Therefore, evaluation of relay setting is crucial. The purpose of this paper is to evaluate the setting of distance relay that was installed at Pamona and Sidera substation. Furthermore, calculation of curent fault and impedance of short circuit was done by intervering fault to the line connected Pamona and Sidera substation in matlab. The method used is simulation using matlab application. The result shows that the highest short circuit current obtained at 25% of the length of Pamona-Sidera transmission line, 6203.47A. The smallest short circuit current was 1255,86A, occurred at 100% of the Keyword : Short Circuit, Distance Relay, Transmission line